The changing role of central banks - Chorafas, Dimitris N. (United States; Palgrave macmillan, 2013)
Brings into perspective financial, political, and social reactions to major economic problems of the last ten years, particularly those pertaining to money and initiatives taken by central banks, and the parallel challenge of bank regulation.
Includes bibliographical references (pages 257-272) and index.
oif 11/06/15
Loan
Keywords: Banks and banking, Central; Monetary policy; Economic policy